2016
DOI: 10.1099/mic.0.000331
|View full text |Cite
|
Sign up to set email alerts
|

Immunodominant membrane proteins of phytoplasmas

Abstract: Phytoplasmas are plant-pathogenic, phloem-colonizing, cell wall-less microorganisms that are primarily dependent on insect transmission for their spread and survival. The life cycle of phytoplasmas involves replication in insects and host plants. Until recently, phytoplasmas have resisted all attempts at cultivation in cell-free media, making these pathogens poorly characterized on a physiological and biochemical basis. However, host-pathogen relationships can be studied by investigating immunodominant membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Interestingly, positive selection acting on phytoplasma MP has been suggested as a key feature in the adaptation of the pathogen to different hosts (Fabre et al ). Strong antigenic properties, previously described for extracellular domains of IDPs (Konnerth et al ), were also confirmed here for FD‐D Imp. Indeed, preliminary unpublished data confirm that the polyclonal serum, raised against the Imp recombinant domain in this study, resulted in specific recognition of the corresponding native full‐length protein in field samples (E. Angelini, pers.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, positive selection acting on phytoplasma MP has been suggested as a key feature in the adaptation of the pathogen to different hosts (Fabre et al ). Strong antigenic properties, previously described for extracellular domains of IDPs (Konnerth et al ), were also confirmed here for FD‐D Imp. Indeed, preliminary unpublished data confirm that the polyclonal serum, raised against the Imp recombinant domain in this study, resulted in specific recognition of the corresponding native full‐length protein in field samples (E. Angelini, pers.…”
Section: Discussionsupporting
confidence: 89%
“…SecY), adhesins, ATP‐dependent proteases and those encoded by potential mobile units and plasmids. However, a number of studies focused on the IDPs, since they are the most abundant proteins of the cell surface of phytoplasmas (for an overview see Konnerth et al ). Previous studies showed that two (Immunodominant membrane protein (Imp) and Antigenic membrane protein (Amp)) of the three nonhomologous immunodominant MP are involved in interactions between the phytoplasma cell surface and insect proteins (Suzuki et al ; Siampour et al , ; Galetto et al ; Rashidi et al ).…”
Section: Introductionmentioning
confidence: 99%
“…A crucial phase of the transmission process is the protein interaction between pathogen cells and those of the host, regulating pathogen crossing of gut and salivary gland epithelia. The main strategy for bacterial internalization reported for plant pathogenic agents is endo‐exocytosis (Kwon et al., ; Hogenhout et al., ; Cicero et al., ), mediated by various membrane proteins (Labroussaa et al., , ; Béven et al., ; Duret et al., ; Konnerth et al., ; Arricau‐Bouvery et al., ). The absence of specific adhesion machinery to host cells seriously weakens the vector competence (Weintraub & Beanland, ).…”
Section: Bacterial Phytopathogen‐vector Relationsmentioning
confidence: 99%
“…The resulting tree had the same topology as the generated by 16S rRNA and ribosomal protein genes, supporting the separation of BellVir phytoplasma (Figure 3). Immunodominant proteins would not be correlated with that of 16Sr DNA; however, imp is a gene well conserved over a wide range of phytoplasmas and can reflect in between phytoplasma differences regarding host range and vector transmission [35]. Phytoplasmas immunodominant proteins have been classified into three distinct types: (i) immunodominant membrane protein (Imp); (ii) immunodominant membrane protein A (IdpA); and (iii) antigenic membrane protein (Amp) [36].…”
Section: Bellvir Represents a Novel Taxon For The Provisional Genus ‘mentioning
confidence: 99%